(untitled) (International Journal of Engineering and Computer Science, 2013)
Obliging Evincible Data Chattels is a technique for ensuring the integrity of data in storage outsourcing. In this paper, we address the construction of an efficient Provable Data Possession scheme for distributed cloud storage to support the scalability of service and data migration, in which we consider the existence of multiple cloud service providers to cooperatively store and maintain the client’s data. We present a cooperative obliging Evincible Data Chattels scheme based on homomorphic verifiable response and hash index hierarchy. We prove the security of our scheme based on multi-prover zero-knowledge proof system. Our paper show that introduces scalability and communication overheads in comparison with non-cooperative approaches. Index Terms: multiple, cloud, services, data scalability, chattels.